Analisys of spatial structure differences in Nógrád County (focus on society and economy) - Víg, Péter; Némediné Kollár, Kitti; Péli, László (Acta Carolus Robertus, 2023)
The socio-economic spatial structure of Hungary has been dominated by significant territorial differences in the approximately thirty years following the change of regime (and even today). In Hungary the territorial disparities/inequalities are gradually increasing. Before the change of regime the era left a deep mark on both Hungary economy and the attitude of the population, the consequences of which are still felt throughout the country and in Nógrád County as well. The spatial location of the county under consideration - which is remote from an infrastructural point of view - did not help all these spatial effects. In our opinion, many people has become even poorer and few richer than before. Social and economic indicators of Nógrád County (unemployment, income per capita, number of enterprises... etc.) mostly lags behind other counties in Hungary, often lagging behind them to a large extent (Baráthi, 2018). In this study, we try to answer the following question: what are the causes of this and what spatial processes determine the current situation? We present Nógrád County and its northern three districts: Salgótarján, Balassagyarmat and Szécsényi districts, with a special focus on Salgótarján. Based on the results of this research, the main goal is to formulate (based on analysing some theoretical and statistical relationships) and to propose the key factors that can move the county out of its current stagnant or declining situation, especially focusing on its northern part.